assessment of the efficacy of tmj arthroscopy-assisted masseter nerve avulsion on hemimasticatory spasm: An original research - A Rashmi Pillai; G Jeevan Kumar; Praveen Kumar; Sarin A Nizar; Siva Kumar Pendyala; Fawaz Abdul Hamid Baig (Wolters Kluwer Medknow Publications, 2023)
The goal of this study is to find a cure for the masticatory muscle disease known as hemimasticatory spasm (HMS). This retrospective investigation intends to find a more efficient therapeutic approach for HMS patients by examining the clinical effectiveness of masseteric nerve avulsion performed on HMS using a temporomandibular arthroscope. A clinical study was piloted where the subjects were treated for masseter nerve avulsion by TMJ arthroscopy. The follow-up was done till 2 years, and the subjects were evaluated for the various characteristics like difficulties, masticatory abilities, and various sounds at the joint for the various functions of the joint. The diagnosis was done using the electrophysiological electromyogram (EMG) at the designated time intervals. There was a complete remission in all the subjects. The masseter nerve avulsion was effective since the scores lowered. Within 3 years of the operation, electrophysiological EMG depicted no discharge potential with a high frequency, and the total efficiency when paired with the clinical effectiveness was deemed acceptable. The maximal masseter power between the treated and nontreated sides was comparable. The mastication, on comparing, was also as effective as the normal side; however, lower mastication was noted in the first year. The avulsed nerve tissues lacked any apparent demyelination. Masseteric nerve avulsion with temporomandibular arthroscope assistance provided acceptable and stable total effectiveness for the intervention of the hemimasticatory spasm. While the strength of the muscle of the afflicted side was only marginally reduced, its masticatory effectiveness was optimally preserved.